2017
DOI: 10.1016/j.jpainsymman.2017.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Mind the Mode: Differences in Paper vs. Web-Based Survey Modes Among Women With Cancer

Abstract: Context Researchers administering surveys seek to balance data quality, sources of error, and practical concerns when selecting an administration mode. Rarely are decisions about survey administration based on the background of study participants, though socio-demographic characteristics like age, education, and race may contribute to participants’ (non)responses. Objectives In this study, we describe differences in paper- and web-based surveys administered in a national cancer survivor study of women with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 14 publications
1
22
0
Order By: Relevance
“…However, we did find that the oldest age group (65 or above) was more likely to respond than the youngest among the paper arm, but we did not observe this for web. This is consistent with prior research finding older individuals overrepresented among responders to a paper survey while web respondents are on average younger [63, 65] and that responders to web surveys are typically younger than those to a paper survey [64]. Due to the continuing relationship between age and web survey response patterns, using web alone to survey cancer survivors may not yet be advisable, especially since the larger population of cancer survivors is on average older than those included in this study, and only 44% of adults age 80 or above use the internet [67].…”
Section: Discussionsupporting
confidence: 92%
“…However, we did find that the oldest age group (65 or above) was more likely to respond than the youngest among the paper arm, but we did not observe this for web. This is consistent with prior research finding older individuals overrepresented among responders to a paper survey while web respondents are on average younger [63, 65] and that responders to web surveys are typically younger than those to a paper survey [64]. Due to the continuing relationship between age and web survey response patterns, using web alone to survey cancer survivors may not yet be advisable, especially since the larger population of cancer survivors is on average older than those included in this study, and only 44% of adults age 80 or above use the internet [67].…”
Section: Discussionsupporting
confidence: 92%
“…This novel hybrid instrument was developed to avoid common problems noted with other scales. These issues include being too lengthy, requiring responses too frequently, prolonged study periods leading to recall bias and lowered compliance, as well as proprietary forms that required payment for use [36][37][38][39]. Subject applicants were then reviewed and approved by the Colorado Center for Health and Sports Science Institutional Review Board (CCHSS IRB), with fourteen (N=14) subjects being accepted into and completing the study.…”
Section: Methodsmentioning
confidence: 99%
“…Pretesting pilot work determined that the total survey completion time estimate = 30-45 minutes. Prior team research (Hagan et al, 2017) has demonstrated that participants find the estimated time of survey completion to be acceptable. *Likert-scaled items from a multi-item scale are ordinal.…”
Section: Ratiomentioning
confidence: 99%